Morphometric and molecular differentiation between quetzal subspecies of Pharomachrus mocinno (Trogoniformes: Trogonidae) - Solórzano, Sofía; Oyama, Ken (Revista de Biología Tropical, 2010)
The resplendent Quetzal (Pharomachrus mocinno) is an endemic Mesoamerican bird species of conservation concern. Within this species, the subspecies P. m. costaricensis and P. m. mocinno, have been recognized by apparent morphometric differences; however, presently there is no sufficient data for confirmation. We analyzed eight morphometric attributes of the body from 41 quetzals: body length, tarsus and cord wing, as well as the length, wide and depth of the bill, body weight; and in the case of the males, the length of the long upper-tail cover feathers. We used multivariate analyses to discriminate morphometric differences between subspecies and contrasted each morphometric attribute between and within subspecies with paired non-parametric Wilcoxon test. In order to review the intraspecific taxonomic status of this bird, we added phylogenetic analysis, and genetic divergence and differentiation based on nucleotide variations in four sequences of mtDNA. The nucleotide variation was estimated in control region, subunit NDH6, and tRNAGlu and tRNAPhe in 26 quetzals from eight localities distributed in five countries. We estimated the genetic divergence and differentiation between subspecies according to a mutation-drift equilibrium model. We obtained the best mutation nucleotide model following the procedure implemented in model test program. We constructed the phylogenetic relationships between subspecies by maximum parsimony and maximum likelihood using PAUP, as well as with Bayesian statistics. The multivariate analyses showed two different morphometric groups, and individuals clustered according to the subspecies that they belong. The paired comparisons between subspecies showed strong differences in most of the attributes analyzed. Along the four mtDNA sequences, we identified 32 nucleotide positions that have a particular nucleotide according to the quetzals subspecies. The genetic divergence and the differentiation was strong and markedly showed two groups within P. mocinno that corresponded to the quetzals subspecies. The model selected for our data was TVM+G. The three phylogenetic methods here used recovered two clear monophyletic clades corresponding to each subspecies, and evidenced a significant and true partition of P. mocinno species into two different genetic, morphometric and ecologic groups. Additionally, according to our calculations, the gene flow between subspecies is interrupted at least from three million years ago. Thus we propose that P. mocinno be divided in two independent species: P. mocinno (Northern species, from Mexico to Nicaragua) and in P. costaricensis (Southern species, Costa Rica and Panama). This new taxonomic classification of the quetzal subspecies allows us to get well conservation achievements because the evaluation about the kind and magnitude of the threats could be more precise.